Exploring Culturally Responsive Teaching (CRT) On Poetry And Drama Class - Ibrahim, Muhammad Bagus; saifulloh, Ahmad Iklil; Mardiana, Wiwik (Philosophiamundi, 2024)
This paper discusses the practice of Culturally Responsive Teaching in a "Poetry and Drama in Language Education" class in one of the universities in Mojokerto, East Java, Indonesia, along with its effect on students' speaking skill in EFL setting. This was a qualitative study that used observations and interviews among students at a university in Mojokerto. This approach involves the use of CRT to make the activities of related poetry and drama materials relevant to the students' cultural background and everyday experiences. The application of CRT greatly enhanced the motivation and participation of students in class and their understanding of the poetry and drama materials. This improved students' critical and analytical thinking that was inductively created through discussions and activities most related to them ontologically. Additionally, students heightened their cultural awareness and appreciation of diverse perspectives, which contributed to the development of an inclusive learning environment. In this regard, application of CRT in learning English has had a positive impact on the students' speaking and collaboration skills and has set a strong base for the development of language skills within a meaningful context of use. The research provides the fact that CRT is a sound approach to making the desired improvements within students' learning outcomes and in their eventual educational applications.